Synthesis and characterization of nanohydroxyapatite (nHAp) from Meretrix Meretrix Clam shells and its in-vitro studies for biomedical applications. (October 2022) - Sindhya, A.; Johnson Jeyakumar, S.; Jothibas, M.; Pugalendhi, P.
Abstract: Recycling of massive waste into valuable products promotes two in one advantages of waste recovery and a pollution-free environment. Preparation of Nanohydroxyapatite (nHAp) and its polymer composites using waste sea shells (natural precursor) are effectively useful in making artificial bone implants, bone cement, and toothpaste additives. The present work is focused to obtain nHAp with good crystalline nature and better biocompatibility using Meretrix Meretrix Clam shells as raw materials by the Co-precipitation method. To enhance the physio-chemical properties, polymers were used as capping agents. The functional group, particle size, thermal stability, phase transition, surface morphology, and electronic transition of atoms of the synthesized samples have been analyzed by spectrographic tools such as FT-IR, XRD, TG/DTA, FESEM/EDAX, XPS and HR-TEM with EDAX mapping respectively. Furthermore, the bacterial sensitivity of the sample against bacteria, the efficiency of the sample towards the formation of an apatite layer over the surface and its hemocompatibility nature were studied by antibacterial, SBF analysis and hemolysis assay respectively. This method of synthesis is free from hard chemicals and harmful by-products. Thus, the report of the present study suggests that it is promising to achieve nHAp with enhanced surface modification which indirectly promotes bone-bonding capability with natural living bone. Highlights: Synthesis of pure and polymer mediated nanohydroxyapatite for making bone and dental implants using natural precursor . First to report, Meretrix Meretrix clam shells were used as a precursor to extract nanohydroxyapatite. This method is free from harmful chemicals such as reactants and toxic residues as a by-product. Potential to prepare nanohydroxyapatite with a high yield on large scale with a minimum budget.